Broadening the Scope of the Flavin‐Tag Method by Improving Flavin Incorporation and Incorporating Flavin Analogs. (19th April 2022) - Tong, Yapei; Loonstra, Marnix R.; Fraaije, Marco W.
Abstract: Methods for facile site‐selective modifications of proteins are in high demand. We have recently shown that a flavin transferase can be used for site‐specific covalent attachment of a chromo‐ and fluorogenic flavin (FMN) to any targeted protein. Although this Flavin‐tag method resulted in efficient labeling of proteins in vitro, labelling in E. coli cells resulted in partial flavin incorporation. It was also restricted in the type of installed label with only one type of flavin, FMN, being incorporated. Here, we report on an extension of the Flavin‐tag method that addresses previous limitations. We demonstrate that co‐expression of FAD synthetase improves the flavin incorporation efficiency, allowing complete flavin‐labeling of a target protein in E. coli cells. Furthermore, we have found that various flavin derivatives and even a nicotinamide can be covalently attached to a target protein, rendering this method even more versatile and valuable. Abstract : Flavin‐tag 2.0 : The Flavin‐tag method can be used for labelling of proteins with various chromo‐ and fluorophores and redox‐active probes, including flavin (yellow), roseoflavin (red), 5‐deazaflavin (fluorescent), and nicotinamide.